2020
DOI: 10.1016/j.invent.2020.100355
|View full text |Cite
|
Sign up to set email alerts
|

Therapist behaviours in a web-based mindfulness-based cognitive therapy (eMBCT) for chronic cancer-related fatigue – Analyses of e-mail correspondence

Abstract: Web-based mindfulness-based cognitive therapy (eMBCT) has been found effective in decreasing fatigue severity in patients suffering from Chronic Cancer-Related Fatigue (CCRF). In web-based therapy, guidance from a therapist positively affects treatment outcome. So far, less is known about what kind of therapist behaviours contribute to treatment outcome. The present study aimed at 1) identifying therapist behaviours during eMBCT and 2) exploring whether these behaviours were correlated to a decrease in fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Several studies have demonstrated the positive effects of eMBI on chronic cancer. It gives patients more time and space for mindfulness training (Maas et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the positive effects of eMBI on chronic cancer. It gives patients more time and space for mindfulness training (Maas et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Character strengths also help meet the needs of others in the social setting of the individual, in addition to contributing to social behavior (Niemiec et al, 2012). Linley et al (2010) claimed that character strength could improve the academic goals of students. The practical principle of mindfulness identified by (Bishop et al, 2006) is that mindfulness requires self-regulation and attention (self-regulation & attention) and an attitude of curiosity, openness, and acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between a counsellor/therapist who performs online-based interventions is that they do not do -teaching‖ or detailed directions such as face-to-face interventions. In particular, clients have the primary responsibility in obtaining theoretical knowledge from reading, watching material on the internet or other sources which are also managed in weekly assignments/weekly modules (Maas et al, 2020) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Parsons et al, [27] results of research conducted with MBCT and MBSR that about 60% of research subjects complete daily tasks at home to which individuals have substantially committed time to practice consistently, although less than suggested in standard format interventions (Maas et al al.,) [30]. Segal et al, [5] the results of the intervention show positive evidence in treatment outcomes even though the significance is small.…”
Section: Discussionmentioning
confidence: 99%